Staff- and service-level factors associated with organisational readiness to implement a clinical pathway for the identification, assessment, and management of anxiety and depression in adults with cancer - Mona M. Faris; Heather L. Shepherd; Phyllis N. Butow; Patrick Kelly; Sharon He; Nicole Rankin; Lindy Masya; The ADAPT Program Group; Joanne Shaw (BMC, 2023)
Abstract Background Organisational readiness is recognised as a key factor impacting the successful translation of research findings into practice. Within psycho-oncology, measuring organisational readiness and understanding factors impacting organisational readiness is crucial as it is often challenging to implement evidence-based findings into routine cancer care. In this quantitative study, we examined the level of organisational readiness of cancer services preparing to implement a clinical pathway for the screening, assessment, and management of anxiety and depression in adult cancer patients (the ADAPT CP) within a cluster randomised controlled trial and sought to identify staff- and service-level factors associated with organisational readiness. Methods Multidisciplinary staff across 12 Australian cancer services were identified. Their perceptions of their services' readiness to implement the ADAPT CP in the cancer stream or treatment modality selected within their service was assessed prior to implementation using the Organizational Readiness for Implementing Change scale. Data collection included staff demographic and professional characteristics, and their perception of the ADAPT CP using a set of 13 study-specific survey items. Service characteristics were captured using a site profile audit form and workflows during site engagement. Results Fourteen staff- and service-level factors were identified as potentially impacting organisational readiness. To identify factors that best explained organisational readiness, separate univariate analyses were conducted for each factor, followed by a backward elimination regression. Compared to services that implemented the ADAPT CP in one treatment modality, those opting for four treatment modalities had significantly higher organisational readiness scores. Staff in administrative/technical support/non-clinical roles had significantly higher organisational readiness scores compared to psychosocial staff. Higher organisational readiness scores were also significantly related to more positive perceptions of the ADAPT CP. Conclusions Readiness to implement an anxiety and depression clinical pathway within 12 oncology services was high. This may be attributed to the extensive engagement with services prior to implementation. The factors associated with organisational readiness highlight the importance of ensuring adequate resourcing and supporting staff to implement change, effectively communicating the value of the change, and taking a whole-of-service approach to implementing the change. Future longitudinal studies may identify factors associated with ongoing readiness and engagement prior to implementation. Trial registration The ADAPT RCT was registered prospectively with the ANZCTR on 22/03/2017. Trial ID ACTRN12617000411347. https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=372486&isReview=true .